Clamped circular plate with a central indentor - Sai, Wei (2016)
This project provides the fundamental study of the axisymmetric circular plate with a central load. The theoretical methods with formulae are generally listed for Kirchhoff Plate Theory, Ritz minimum energy and Chian Weizang’s large deformation for plates. The finite element simulations have done for the aluminum circular plate and glass laminate aluminum reinforced epoxy (GLARE) which is is a fiber metal laminate under a lateral undeformable indentation using ANSYS Workbench. Since highly non-linear simulations are involved, very small time steps are required to overcome the difficulties in convergence. In such cases, explicit method is applied for both aluminum and GLARE circular plate with clamped edges. Two ways of simulation were discovered by applying velocity or displacement to the indentor. It is found the simulation results are much more stable when to apply a defined displacement to the indentor and observe the reaction load through the clamped circular plate edge. The explicit dynamics simulation of the aluminum plate shown that the results are quite close to the theoretical study by Chian Weizang’s paper for the initial part of the response. The simulation results for GLARE shown a good match with the theoretical plot derived by Ritz method. By doing this study of simulation, it could save the number of actual experiment testing and make the experiment become more specific and objective. By altering the material composition and layout of GLARE, the capability of resistance towards indentation, impact loading could be improved through FEA modeling which would be quite meaningful for future material and structure development for aerospace industries.